Pelaksanaan Perlindungan Lahan Pertanian Pangan Berkelanjutan Berdasarkan Regulasi Rencana Tata Ruang - Ulfa Nur Oktiana; Waluyo Waluyo; Asianto Nugroho (Jurnal Discretie, 2020)
This study aims to determine the implementation of sustainable food agriculture land protection in Sleman Regency based on Regional Regulation No. 12 of 2012 concerning the Sleman Regency Regional Spatial Plan 2011-2031, as well as the obstacles of the Sleman Regency Government in establishing Sustainable Food Agricultural Land Protection Areas. This research is an empirical study. The data source used in this study came from primary data, which were the results of interviews with Civil Servants in the Agriculture and Fisheries Office of the Sleman Regency and the Sleman Regency Regional Development Planning Agency. Supported by secondary data consisting of primary legal materials and secondary legal materials. The results of research related to the implementation of sustainable food agriculture land protection in Sleman Regency shows that the spatial regulation of the Sleman Regency is only limited to efforts to control land conversion as a protection effort, there has been no determination of sustainable food agriculture areas due to various obstacles. In the implementation of the spatial planning policy is not enough to control the rate of conversion of agricultural land.